Minute mysteries : brainteasers, puzzlers, and stories to solve - Hirsch, Jennifer; Witkowski, Teri. ([Middleton, WI] : Pleasant Co., 2006)
Thirteen brief stories that leave the American Girl featured in each puzzling about something, and the reader is asked to find the answers using clues in the stories. Answers provided in the back of the book.
Ages 8+.
Keywords: Literary recreations -- Juvenile literature; Logic puzzles -- Juvenile literature; Riddles, Juvenile; Literary recreations; Logic puzzles; Riddles